Volatile and carbohydrate composition of rare unifloral honeys from Spain - Delafuente, E.; Sanz, M.; Martinezcastro, I.; Sanz, J.; Ruizmatute, A. (Food Chemistry, 2007)
Volatile composition and carbohydrate content of Spanish honey samples from uncommon botanical origins have been studied by gas chromatography coupled to mass spectrometry. About 100 volatile compounds were identiﬁed; some of them appeared to be characteristic of particular honey types, such as methyl salycilate in willow (Salix spp.), 2,6,6-trimethyl-2,4-cycloheptadien-1-one (eucarvone) in almond tree (Prunus dulcis) and isophorone in strawberry-tree (Arbutus unedo). Concentration ranges for major carbohydrates were similar to those previously reported in other honeys with diﬀerent botanical origins, although concentrations of maltulose in avocado honeys (Persea americana) and of melezitose in Quercus ilex honeys were higher. Some carbohydrate alcohols could also be considered as markers of honey botanical origin, such as quercitol for Q. ilex and perseitol for avocado.
Keywords: carbohydrates; gc; GC-MS; honey; ms; polyalcohols; volatile compounds